Single-machine scheduling with truncated sum-of-processing-times-based learning effect including proportional delivery times. Issue 4 (May 2016) - Wu, Yu-Bin; Wang, Jian-Jun
Abstract The single-machine scheduling problem with truncated sum-of-processing-times-based learning effect and past-sequence-dependent job delivery times is considered. Each job's delivery time depends on its waiting time of processing. For some regular objective functions, it is proved that the problems can be solved by the smallest processing time first rule. For some special cases of the total weighted completion time and the maximum lateness objective functions, the thesis shows that the problems can be solved in polynomial time.